The U.S. maritime strategy in the North Atlantic and Norwegian Sea: an evolving strategy in need of reassesment - Woodard, Jimmy Clifford. (Monterey, California. Naval Postgraduate School, 1991)
This thesis examines the evolution, and theoretical basis of the United States' maritime strategy in the North Atlantic and what is referred to as NATO's Northern Flank. The strategy associated with past Secretary of the Navy, John Lehman, is no longer considered applicable in the context of today's East-west relationship and is in need of reassessment. The paper then assesses the current, post Cold War situation and looks at future security interests the United States may have in the region. Additionally, the security and defense capabilities of our allies in the region are examined. Given the United States will remain closely linked with European security issues, by examining the successes and failures of past strategies and the strengths and weaknesses of our allies, one will be better able to develop a new strategy. Approved for public release; distribution is unlimited. Lieutenant Commander, United States Navy http://archive.org/details/theusmaritimestr1094543754